2023
DOI: 10.1177/1934578x221148621
|View full text |Cite
|
Sign up to set email alerts
|

Two New Nitrogen-Containing Glycosides From Stixis scandens

Abstract: Phytochemical investigation of a methanol extract of Stixis scandens stems and leaves led to the isolation of 3 nitrogen-containing compounds (1-3) and 6 phenolics (4-9), which included 2 new glycosides, one a phenolic amide glucoside, scandemide (1), and the other an indole alkaloid glycoside, stixilenin (2). Their structures were elucidated by spectroscopic (1D- and 2D-NMR) and spectrometric (HR-ESI-MS) analyses, and acid hydrolysis. The isolated compounds were evaluated for their inhibitory effects on nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The different parts of Stixis species are used in folk medicine to treat rheumatism, arthralgia, and eye diseases. 4,5 In previous studies, isolated compounds, including alkaloids, 6 L-stachydrine, flavonoids, lignans, phenolic amides, 7 glucosinolates, 8 and other compounds, were found in Stixis species. Recently, modern pharmacological reports showed that extracts and phytocompounds of Stixis species exhibited various pharmacological effects such as anti-inflammatory, 7 antiviral effects, 9 etc.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…The different parts of Stixis species are used in folk medicine to treat rheumatism, arthralgia, and eye diseases. 4,5 In previous studies, isolated compounds, including alkaloids, 6 L-stachydrine, flavonoids, lignans, phenolic amides, 7 glucosinolates, 8 and other compounds, were found in Stixis species. Recently, modern pharmacological reports showed that extracts and phytocompounds of Stixis species exhibited various pharmacological effects such as anti-inflammatory, 7 antiviral effects, 9 etc.…”
Section: Introductionmentioning
confidence: 94%
“…The primary distribution of S. suaveolens species includes China (Guangdong, West Guangxi, Hainan, South Xizang, South Yunnan, and Southwest Yunnan), Northeast India, Bangladesh, Bhutan, Myanmar, Nepal, North and Northeast Thailand, Cambodia, Laos, and Northwest Vietnam (Lai Chau, Son La, and Ha Giang). [4][5][6][7][8][9][10]18,19 Morphologically, the woody vines of S. suaveolens are 1.0 to 15.0 m tall. Twigs are stout, terete, light red, and have smooth hair.…”
Section: Morphological Features and Geographical Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2023 publication showed two new N-containing glycoside compounds in the composition of Stixis scandens leaves. 12 A similar plant, Stixis suaveolens Roxb, in the same family, has been studied for some of its chemical components. 13 From the Stixis suaveolens Roxb plant, Vietnamese scientists have developed a method to extract the compound Cappariloside A.…”
Section: Introductionmentioning
confidence: 99%